Imaging Findings of an Unusually Located Hydatid Cyst Presented as a Sacrococcygeal Mass - Yilmaz, Guliz (Iran J Radiol, 2015)
Hydatid disease (HD) is a parasitic infection that is most commonly caused by the larval stage of Echinococcus granulosus. Unusual location for this disease can cause diagnostic and therapeutic problems. We herein report a case of sacrococcygeal HD at an unusual location in a 30-year-old woman. She was evaluated using computed tomography (CT) imaging and magnetic resonance imaging (MRI) after the demonstration of the lucent bone lesion on plain pelvic radiography. There was an expansile lytic mass without contrast enhancement suggesting a cystic mass in the sacrococcygeal region. Medical history revealed that she had undergone surgery for liver HD and the serological test results were diagnostic for HD. In light of this, no surgery was carried out for this cystic mass and she was followed with the diagnosis of sacrococcygeal HD.